Bamboo Design Training for hotel and culinary amenities at the Bamboo Community of Sukabumi Regency - Sabrina O. Sihombing; Juliana Juliana; Ira B. Hubner; Rudy Pramono; July Hidayat (Penerbit Goodwood, 2023)
Purpose: Bamboo is an economic potential that is not only derived from the bamboo product itself but can also be expanded into an attractive natural tourist spot. Unfortunately, the potential of bamboo as a product is often focused on the functional and forgets the unique creations for the product that can increase the value of the product itself. The training conducted between Pelita Harapan University and Bamboo Community Dunia Bambu Sejahtera (DBS) aims to provide understanding and knowledge related to creative bamboo designs to meet the market for hotel and culinary amenities. Methodology/approach: The training is done by dividing the group. Each group is taught various bamboo creations. During the training, participants were also given the opportunity to discuss about bamboo and the potential for creative creations that can be made to attract market attention. Results/findings: Training participants gain additional knowledge about bamboo and its unique and creative bamboo creations. The results of the evaluation before and after the training showed that the participants felt that they had gained knowledge that could be integrated into making bamboo crafts. Conclusion: With this training, it is hoped that the craftsmen can improve their weaving skills which in turn will have an impact on increasing product sales and the income of the craftsmen themselves